Features of the super prism effect in multilayer dielectric coatings - Pervak, Yu.A.; Onitchuk, V.M.; Pervak, V.Yu. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
We demonstrate that the strong change of reflected beam intensity in the spectral range of the super-prism effect not allow to use periodic multilayer coatings as effective wavelength division multiplexing devices. But using chirped mirrors that are one of the key elements in ultrafast optics can solve this problem with success.